Pelestarian Tradisi Bersih Desa di Tengah Perubahan Sosial dan Modernisasi di Desa Ploso - Rochmawati, Reni; Trisnayana, Wahida Emisa; Al Bayani, Raden Syaifudin (Lembaga Yasin AlSys, 2025)
The Bersih Desa tradition is a form of cultural heritage that continues to be preserved by the community of Ploso Village, Ngawi Regency, as an expression of gratitude and respect toward ancestors. However, amid the rapid currents of modernization, this tradition faces serious challenges, particularly the declining participation of younger generations. This study aims to examine the implementation, socio-spiritual meaning, and preservation challenges of the Bersih Desa tradition in the context of social change. A descriptive qualitative method was employed, with data collected through participatory observation, in-depth interviews, and documentation. Analysis was conducted interactively using triangulation techniques to ensure data validity. The findings show that although the tradition is still regularly performed and holds significant spiritual and social value, there is a shift in perception among the youth, who tend to view it as less relevant. These findings highlight the need for educational and collaborative approaches to engage younger generations, ensuring the tradition’s adaptive preservation. This study contributes to the strengthening of local cultural discourse and recommends the integration of local wisdom values into educational programs and community activities to sustain the tradition amid evolving social dynamics.